2017
DOI: 10.3389/fmicb.2017.01645
|View full text |Cite
|
Sign up to set email alerts
|

Seed and Root Endophytic Fungi in a Range Expanding and a Related Plant Species

Abstract: Climate change is accelerating the spread of plants and their associated species to new ranges. The differences in range shift capacity of the various types of species may disrupt long-term co-evolved relationships especially those belowground, however, this may be less so for seed-borne endophytic microbes. We collected seeds and soil of the range-expanding Centaurea stoebe and the congeneric Centaurea jacea from three populations growing in Slovenia (native range of both Centaurea species) and the Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 73 publications
2
32
0
2
Order By: Relevance
“…These results suggest different responses of nematodes to range-expanding C. stoebe in the new compared to the original range, as has also been demonstrated for its seed-and root-associated fungal communities (Geisen et al, 2017). One of the four range-expanding plant species, C. stoebe, showed a stronger shift in genus-level nematode community composition between the original range in Central Europe and the new range in North-Western Europe than the congeneric native C. jacea.…”
Section: Discussionsupporting
confidence: 61%
“…These results suggest different responses of nematodes to range-expanding C. stoebe in the new compared to the original range, as has also been demonstrated for its seed-and root-associated fungal communities (Geisen et al, 2017). One of the four range-expanding plant species, C. stoebe, showed a stronger shift in genus-level nematode community composition between the original range in Central Europe and the new range in North-Western Europe than the congeneric native C. jacea.…”
Section: Discussionsupporting
confidence: 61%
“…and Cladosporium sp.) were recovered from seeds, and both are reported elsewhere as seed endophytes (Hodgson et al 2014;Geisen et al 2017).…”
Section: R a F Tmentioning
confidence: 99%
“…Endophytic fungi commonly have been categorized into two groups based on their manner of transmission: vertically transmitted endophytes (VTEs, e.g., Neotyphodium) that inhabit temperate grasses (Lolium) and are transmitted from the mother plant (Müller and Krauss, 2005) and horizontally transmitted endophytes (HTEs) transmitted mostly via spores from plant to plant (Arnold, 2007). Previous studies on native plants and crops indicated that fungal endophyte communities varied based on host genotypes (Emi and Kenji, 2013), plant tissues (Wearn et al, 2012), growth stages (Shi et al, 2016), and distribution areas (Geisen et al, 2017). However, most reports to date have addressed VTEs when exploring the endophytes of invasive plants (Rudgers et al, 2005); only very few studies have focused on the interaction between HTEs and invasive plants (Newcombe et al, 2009;Aschehoug et al, 2012).…”
Section: Introductionmentioning
confidence: 99%